2021
DOI: 10.1177/00812463211025466
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the employability and employment destinations of professional psychology alumni

Abstract: Professional training in psychology typically focuses on competencies and learning outcomes. However, this does not necessarily translate into long-term employability. Graduate tracer studies are recommended for exploring employment destinations and employability. Graduate tracer studies are noted to be of particular use for investigating health professionals’ career paths and examining field-specific issues. The reported study examined the employability and employment destinations of 29 alumni from two psycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Statistics from China's Ministry of Education of the People's Republic of China (n.d.) showed that the number of college students in China was 30.32 million in 2019, and as of 2022 had risen as high as 36.56 million, with rural college students accounting for about 47% of the total. The above data is evidence of the high growth rate in the number of college students in China in recent years, and the number of employed people is also increasing (Senekal and Smith, 2022;Yin, 2022). However, there is no large-scale postgraduate expansion and recruitment program in China, which leads to a grim employment situation for college students (Pei, 2021;Li, 2022;Xiong et al, 2022;Zhi, 2023).…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Statistics from China's Ministry of Education of the People's Republic of China (n.d.) showed that the number of college students in China was 30.32 million in 2019, and as of 2022 had risen as high as 36.56 million, with rural college students accounting for about 47% of the total. The above data is evidence of the high growth rate in the number of college students in China in recent years, and the number of employed people is also increasing (Senekal and Smith, 2022;Yin, 2022). However, there is no large-scale postgraduate expansion and recruitment program in China, which leads to a grim employment situation for college students (Pei, 2021;Li, 2022;Xiong et al, 2022;Zhi, 2023).…”
Section: Introductionmentioning
confidence: 90%
“…Employment psychology plays an important role in the lives, studies, employment, and career choices of college students ( Hernández-Sánchez et al, 2020 ). Previous studies have shown that good employment psychology can help mobilize college students’ strong learning motivation and improve their comprehensive ability to adapt to the employment environment in China ( Luciano et al, 2021 ; Senekal and Smith, 2022 ). In contrast, poor employment psychology affects college students’ thinking patterns and memory and reduces their employment competitiveness ( Jackson and Tomlinson, 2020 ; Wan Mohd Yunus et al, 2021 ; Peng et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…HEIs must ensure that their curriculum equips students with both theoretical knowledge and practical skills that meet industry demands. This requires a continuous evaluation and adaptation of educational programs to keep pace with industry developments (Senekal, 2018).…”
Section: Skills and Curriculum Alignmentmentioning
confidence: 99%